2022
DOI: 10.3390/microorganisms10020362
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Herpes Simplex Virus Type 1 (HSV-1) Detected on Bronchoalveolar Lavage Fluid (BALF) Samples in Critically Ill COVID-19 Patients Undergoing Invasive Mechanical Ventilation: Preliminary Results from Two Italian Centers

Abstract: Reactivation of herpes simplex virus type 1 (HSV-1) has been described in critically ill patients with coronavirus disease 2019 (COVID-19) pneumonia. In the present two-center retrospective experience, we primarily aimed to assess the cumulative risk of HSV-1 reactivation detected on bronchoalveolar fluid (BALF) samples in invasively ventilated COVID-19 patients with worsening respiratory function. The secondary objectives were the identification of predictors for HSV-1 reactivation and the assessment of its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…HSV-1 is a double-stranded DNA alpha herpesvirus that instigates a lifelong infection within their hosts, establishing a latent infection and reactivating when the host immune system is weakened. We previously observed that as many as 25% of mechanically ventilated COVID-19 patients may reactivate HSV-1 in their low respiratory tract after 30 days of intensive care [ 15 ]. In a similar way, Franceschini observed that up to 30% of patients with severe/critical SARS-CoV-2 pneumonia experienced HSV-1 DNAemia, with 62% of them showing clinically relevant manifestations of HSV-1 infection [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…HSV-1 is a double-stranded DNA alpha herpesvirus that instigates a lifelong infection within their hosts, establishing a latent infection and reactivating when the host immune system is weakened. We previously observed that as many as 25% of mechanically ventilated COVID-19 patients may reactivate HSV-1 in their low respiratory tract after 30 days of intensive care [ 15 ]. In a similar way, Franceschini observed that up to 30% of patients with severe/critical SARS-CoV-2 pneumonia experienced HSV-1 DNAemia, with 62% of them showing clinically relevant manifestations of HSV-1 infection [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective study, we also assessed the cumulative risk of HSV-1 reactivation detected on BALF samples in critically ill patients with COVID-19, by means of PCR [ 15 ]. HSV-1 reactivation was defined in the presence of HSV-1 DNA ≥ 10 4 copies/ml on BALF samples in the presence of worsening respiratory function.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations